Jasmonic acid-mediated cell wall biosynthesis pathway involved in pepper (Capsicum annuum) defense response to Ralstonia solanacearum - Xinwei Jiang; Xinyi Liu; Bin Chen; Xiaofen Zhang; Yihao Wang; Ting Wang; Sansheng Geng; Biao Zhu; Heshan Du (BMC Plant Biology)
Abstract Ralstonia solanacearum is a destructive soil-borne pathogen that causes severe bacterial wilt (BW) disease in peppers. Phytohormone signaling pathways, including those mediated by jasmonic acid (JA), are crucial to plant defense responses against pathogen attacks. Nevertheless, the function of JA in the resistance response of pepper to R. solanacearum is unclear. Therefore, RNA sequencing (RNA-seq) and phytohormone determination experiments were performed to compare the dynamic transcriptome changes and differences in JA and salicylic acid (SA) contents between the resistant pepper line BVRC1 and the susceptible pepper line BVRC25 during R. solanacearum infection. The number of differentially expressed genes (DEGs) was greater in BVRC1 than in BVRC25 at 12, 24, 48, and 72 h post-infection. JA concentrations were also markedly elevated in BVRC1 in response to R. solanacearum. Four distinct co-expression modules and hub genes were identified using weighted gene co-expression network analysis. Exogenous application of JA significantly delayed the onset of R. solanacearum infection and reduced symptom severity in BVRC25. RNA-seq was performed on the resistant pepper line BVRC1 at 24 h post exogenous JA application. GO analysis revealed DEGs enriched in the cell wall biosynthesis-related pathway of BVRC1 after JA treatment. Notably, a pathogenesis-related protein, Capana08g002211, exhibited common up-regulated patterns in response to JA treatment and R. solanacearum infection. A yeast-2-hybrid assay and luciferase complementation imaging assay demonstrated that Capana08g002211 interacted with type III effector (RipTPS). These results demonstrate that the pepper JA-mediated cell wall synthesis pathway participates in the defense response to R. solanacearum.